Uji Kelayakan Buku Ajar Matematika Dasar Terintegrasi Challenge Based on Blended Learning untuk Meningkatkan Kemampuan Bepikir Kreatif - Ardiansyah, Adi Satrio; Sari, Salsabilla Naura; Hamidah, Faridah Shawatul (Universitas Dr. Soetomo, 2021)
Abstract Basic Mathematics is one of the fundamental courses for students in various study programs. Mastery of this material needs to be supported by the selection of learning models and adjusted to the need for IT-based learning innovations. It is also necessary to develop student creativity, especially mathematical creativity, which is the challenges for graduates in the Industrial Era. For this reason, it is necessary to develop a Basic Mathematics Textbook that is integrated with the Challenge Based on Blended Learning (CB-BL) model to answer all these problems. This study aims to determine the feasibility test of these product. Development research with the 4D model was carried out where one of the stages was the Development, which tested the feasibility of the product through a questionnaire from several experts in mathematics and mathematics education. The results of the feasibility test were analyzed using descriptive statistics to determine the criteria for product development results. The results show that the Basic Mathematics Textbook integrated with the CB-BL model meets the feasibility test with a score of 90.48 (Very Eligible Criteria). Thus the Basic Mathematics Textbook integrated with the CB-BL model can be tested in class. Keywords: Blended Learning, Challenge Based Learning, Challenge Based on Blended Learning, Creative Thinking Skills. Abstrak Matematika Dasar merupakan salah satu mata kuliah dasar bagi mahasiswa di berbagai program studi. Penguasaan materi tersebut perlu ditunjang dengan pemilihan model pembelajaran serta disesuaikan dengan kebutuhan akan inovasi pembelajaran berbasi IT. Selain itu, perlu pengembangan kreativitas mahasiswa khususnya kreativitas matematika merupakan tantangan bagi lulusan di era revolusi 4.0. Untuk itu perlu dikembangkan Buku Ajar Matematika Dasar yang terintegrasi dengan model Challenge Based on Blended Learning (CB-BL) untuk menjawab semua permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui uji kelayakan dari pengembangan produk buku ajar tersebut. Penelitian pengembangan dengan model 4D dilaksanakan dimana salah satu tahapnya adalah pengembangan (Development) yang menguji kelayakan produk melalui angket beberapa ahli bidang pendidikan matematika dan matematika. Hasil uji kelayakan dianalisis dengan menggunakan statistik deskriptif untuk mengetahui kriteria hasil pengembangan produk. Hasil uji kelayakan menunjukkan bahwa Buku Ajar Matematika Dasar yang terintegrasi model CB-BL memenuhi uji kelayakan dengan skor 90.48 (kriteria Sangat Layak). Dengan demikian Buku Ajar Matematika Dasar yang terintegrasi model CB-BL dapat diuji coba di kelas. Kata Kunci: Blended Learning, Challenge Based Learning, Challenge Based on Blended Learning, Kemampuan Berpikir Kreatif.